Mengapa Sepak Bola Menjadi Populer di Kalangan Siswa Sekolah Dasar? - Mulyana, Agus; Shafira, Diva; Aditya, Ferdino Arief; Anggia, Intan Ratu; Haq, Mohamad Arinal; Daud, Muhammada Rafi Bahiruddin; Putri, Nasya Nurlillah Kusuma; Ardhiyansah, Saiful (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to identify and analyze the factors that cause elementary school children's interest in football to increase. This study uses a qualitative approach with a literature review method. The data collection process is carried out through scientific journals, books, and research reports that focus on research. The search was conducted through academic databases such as Google Scholar, PubMed, and other online journal portals Using relevant keywords such as